Changes in employment status up to 5 years after breast cancer diagnosis: A prospective cohort study. (December 2019) - Monteiro, Isabel; Morais, Samantha; Costa, Ana Rute; Lopes-Conceição, Luisa; Araújo, Natália; Fontes, Filipa; Dias, Teresa; Pereira, Susana; Lunet, Nuno
Abstract: Aim: To assess how sociodemographic, clinical and treatment characteristics impact employment status five-years following a breast cancer diagnosis, and to compare the incidence rate of changes with the general population. Methods: A total of 462 women with incident breast cancer were evaluated before treatment and three- and five-years later. Adjusted odds ratios (ORs) with 95% confidence intervals (95%CIs) were computed through multinomial logistic regression. Data for comparisons were retrieved from the SHARE Project. Incidence rate ratios (IRRs) with 95%CIs were calculated using Poisson regression. Results: Among the 242 employed women prior to diagnosis, 162 remained employed, 26 became unemployed, 27 entered early retirement, 14 entered normal retirement and 13 were on sick leave at five-years. Unemployment increased with age (≥55 vs < 55 years: OR = 4.49, 95%CI:1.56–12.92; OR = 3.40, 95%CI:1.05–10.97 at three- and five-years, respectively) and decreased with education (>4 vs ≤ 4 years: OR = 0.36, 95%CI:0.13–0.97; OR = 0.27, 95%CI:0.10–0.71 at three- and five-years, respectively). Axillary surgery (unemployment at five-years: OR = 5.13, 95%CI:1.30–20.27), hormonal therapy (unemployment at three-years: OR = 0.28, 95%CI:0.10–0.83) and targeted therapy (sick leave at three-years: OR = 3.79, 95%CI:1.14–12.63) also influenced employment status. Five-years post diagnosis, women with breast cancer had a lower incidence of unemployment (IRR = 0.51, 95%CI:0.30–0.89) than the general population, while, among older women, there was a higher tendency to enter early retirement (IRR = 1.72, 95%CI:0.82–3.61). Conclusions: Although not all women may want to pursue or continue a professional life following their breast cancer experience; those who do may benefit from social and employer support when returning to work. Highlights: Older and less educated women were more likely to be unemployed. Axillary surgery was associated with employment status five years post diagnosis. Patients had a lower incidence of unemployment than the general population. Among older women, patients had a higher incidence of early retirement. Patients may benefit from social and employer support when returning to work.